2017
DOI: 10.1111/josh.12531
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance in Primary School Children With Common Emotional and Behavioral Problems

Abstract: Boys with emotional and behavioral problems in mid-primary school were 12 months behind their peers. Children with emotional and behavioral problems are at high risk for academic failure, and this risk is evident in mid-primary school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 36 publications
(74 reference statements)
2
28
1
11
Order By: Relevance
“…34 Alternatively, there may be common underlying factors that influence educational achievement as well as bullying, such as emotional problems and SES. 18,19,35 However, in the current study, adjustment for emotional problems and SES did little to diminish the associations, but the possibility of confounding cannot be excluded. Also, bullying often occurs within school, which might reduce the victims' connection to school and in turn lead to absences from school, further increasing the risk to academic performance.…”
Section: Discussioncontrasting
confidence: 70%
“…34 Alternatively, there may be common underlying factors that influence educational achievement as well as bullying, such as emotional problems and SES. 18,19,35 However, in the current study, adjustment for emotional problems and SES did little to diminish the associations, but the possibility of confounding cannot be excluded. Also, bullying often occurs within school, which might reduce the victims' connection to school and in turn lead to absences from school, further increasing the risk to academic performance.…”
Section: Discussioncontrasting
confidence: 70%
“…Some studies investigated the relations between internalizing behavioral difficulties and learning difficulties. Mundy et al [14] found a significant relationship between emotional problems and reading and mathematical abilities while Wu et al [23] did not confirm a correlation between anxiety symptoms and performance in mathematics. Internalizing symptoms have been systematically reported in developmental dyslexia (for a review, see Mugnaini and colleagues [24]).…”
Section: Introductionmentioning
confidence: 95%
“…The co-occurrence of emotional-behavioral and learning difficulties has been documented by several studies in both clinical settings and in typical development, the latter focused on dimensional quantitative traits. Mundy et al [14] reported, in a community sample of 1239 Australian primary school children, that about one out of five boys and one out of seven girls displayed emotional or behavioral problems (behavioral screening questionnaire), together with significant delays in literacy and mathematic skills.…”
Section: Introductionmentioning
confidence: 99%
“…When examining associations between concurrent media use and academic performance, we control for both baseline media use and academic performance, which allows an estimate of the effect of concurrent media regardless of prior media use. In secondary analyses we controlled for variables known to be associated with both screen time and academic performance, namely emotional and behavioural problems [40,41] and body mass index [42,43].…”
Section: Introductionmentioning
confidence: 99%